Geração de pulsos ultracurtos com acoplamento de modos híbrido em um laser de fibras ópticas mantenedoras de polarização - Aiub, Eduardo José (2020)
A main motivation for this doctoral thesis was the recent use of lasers with ultrashort pulses being used in ultra-fast optical transmission systems (above 1 Tbit/s). For this, ultrashort pulse generation was demonstrated in two different lasers, one with SMF fibers for the ultrashort pulses generation using the hybrid mode-locking technique and the other with all components and fibers polarization maintaining (all-PM) for short pulses in Q-Switching Mode Locking regime. In the SMF laser, operating in hybrid mode-locking,the main innovation of the work was the use of two-dimensional materials as a saturable absorber at a repetition rate of 40 GHz, using two samples of CVD graphene and one of molybdenum disulfide. The results obtained were pulses with a duration of 655 and 620 fs with CVD graphene and 425 fs with MoS2. It is worth mentioning that, these results contribute to the state of the art as the first measurements of ultrashort pulses using 2D materials at a repetition rate of 40 GHz. In the all-PM laser, which was built to minimize laser instability and separate the possible presence of non-linear polarization rotation (NPR) existing in laser results with standard fibers,the main innovation was the use of CVD graphene deposited on D-shaped PM fiber and as a result, short pulses were obtained for the first time in Q-Switching regime. The challenge of this work was to build a laser capable of operating at a repetition rate of 40 GHz using two-dimensional materials as a saturable absorber and the construction of an all-PM laser for better stability